2019
DOI: 10.1176/appi.neuropsych.17110338
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Right Repetitive Transcranial Magnetic Stimulation for the Treatment of Depression After Traumatic Brain Injury: A Randomized Sham-Controlled Pilot Study

Abstract: Objective: Major depression is the most common psychiatric sequela of traumatic brain injury (TBI), but effective treatment continues to be a challenge, with few studies providing guidance.Methods: In a pilot study, the authors evaluated the effect size of low-frequency right-sided (LFR) repetitive transcranial magnetic stimulation (rTMS), compared with sham treatment, over the right dorsolateral prefrontal cortex (DLPFC) in patients (N=30) with TBI depression and co-occurring neuropsychiatric symptoms, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 52 publications
0
70
0
Order By: Relevance
“…Three studies recruited patients with PCS evaluated by using the self-reported Rivermead Post-Concussion Symptom Questionnaire (RPQ-3 and RPQ-13) 23,26,28 .…”
Section: Postconcussion Syndromementioning
confidence: 99%
See 4 more Smart Citations
“…Three studies recruited patients with PCS evaluated by using the self-reported Rivermead Post-Concussion Symptom Questionnaire (RPQ-3 and RPQ-13) 23,26,28 .…”
Section: Postconcussion Syndromementioning
confidence: 99%
“…Because depression improvement could confound the measurement of somatic symptoms (i.e., PCS), such deviations may have increased bias risk in outcome assessment in two studies 23,28 . Four articles had risk of bias due to high drop-out or loss-to-follow-up rates (>5%) 16,23,24,26 . The study by Lee et al had a high risk of bias of outcome measurement owing to unblinded assessors 25…”
Section: Study Qualitymentioning
confidence: 99%
See 3 more Smart Citations